2018
DOI: 10.4187/respcare.05961
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula in Pediatric Patients: A Survey of Clinical Practice

Abstract: There was no consensus on the definition of HFNC, how to set initial flow, or how to make adjustments. Aerosols were delivered by 75% of respondents, predominantly via a vibrating mesh nebulizer placed on the dry side of the humidifier. The definition of HFNC, how to set flow, and aerosolized medication delivery are areas in which more research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…In‐line placement of a nebulizer with HFNC has been described to solve the difficulty and has attracted attention from clinicians in recent years . The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC . Pediatric patients were reported to be more comfortable and less anxious after inhaling aerosol bronchodilator via HFNC, which has also shown the potential benefits of avoiding intubation in a group of pediatric asthma patients, 26% of whom already had acidosis at PICU admission …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In‐line placement of a nebulizer with HFNC has been described to solve the difficulty and has attracted attention from clinicians in recent years . The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC . Pediatric patients were reported to be more comfortable and less anxious after inhaling aerosol bronchodilator via HFNC, which has also shown the potential benefits of avoiding intubation in a group of pediatric asthma patients, 26% of whom already had acidosis at PICU admission …”
Section: Introductionmentioning
confidence: 99%
“…8,9,[11][12][13] The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC. 14 Pediatric patients were reported to be more comfortable and less anxious after inhaling aerosol bronchodilator via HFNC, 8,9 which has also shown the potential benefits of avoiding intubation in a group of pediatric asthma patients, 26% of whom already had acidosis at PICU admission. 11 Aerosol delivery via HFNC for pediatric patients has been characterized by means of in vitro 10,[15][16][17][18] and radiolabeled in vivo studies.…”
mentioning
confidence: 99%
“…10 The observation that toddlers better tolerate nasal oxygen administration than mask has led to the in-line placement of nebulizers with high-flow nasal cannula (HFNC) devices for transnasal pulmonary delivery. [11][12][13][14] This approach combines benefits of patient's acceptance to receive aerosolized medication for extended dosing periods with the effects of heated humidified gas at the high-flow rate, which has been shown to reduce the patients' work of breathing and improve ventilation. 15,16 Vibrating mesh nebulizer (VMN) is preferred during aerosol delivery via HFNC due to no gas required to generate an aerosol, negligible residual volume, and quiet operation.…”
Section: Introductionmentioning
confidence: 99%
“…A survey among American Pediatric respiratory therapists showed that out of 75% of respondents who administered aerosol therapy during HFNC, 77% delivered aerosol via VMN and 23% removed the patient from HFNC for the aerosol delivery. Thirteen percent of them decreased HFNC flow to improve aerosol delivery …”
mentioning
confidence: 99%
“…Thirteen percent of them decreased HFNC flow to improve aerosol delivery. 6 Aerosol administration via high-flow nasal cannula is a new and innovative approach in pediatric pulmonology; yet, there is lack of consistent data regarding the particle deposition in the lungs particularly when using high-flow rates, often close to 2 to 3 L/kg/min for critically ill children. The heated humidification can further affect the particle size and cause gravimetric sedimentation 7 thereby decreasing pulmonary delivery.…”
mentioning
confidence: 99%